PERTANGGUNGJAWABAN PERDATA MALAPRAKTIK MEDIK (Jurnal Magister Hukum Perspektif, 2021)
This paper aims to discuss civil liability for medical malpractice. The patient's alleged insanity is often considered the negligence of the doctor in carrying out medical actions. The paradigm is getting stronger with increasing reports of medical malpractice every year. Doctors in performing medical treatment of patients are based on a bond or relationship in the agreement. The bond or relationship in the agreement is called inspannings verbentenis or maximal effort engagement. The existence of this shows that the main obligation of a doctor is to do a hard effort that must be done and needed to support the patient. This can be based on the standards of the medical profession and its operational standart as stipulated in article 50 juncto 51 of Law No. 29 of 2004 concerning the Practice of Medicine. The methods used in this study are juridical-normative with a statutory approach. The result obtained is civil liability in a medical malpractice arises if there is wrong treatment from the doctor in relation to providing medical service performance and the patient suffers losses for the doctor's actions. Legal liability in the civil domain is generally realized in the form of compensation or compensation by doctors or hospitals with due regard to the principles of liability. The right of patients in demanding compensation is regulated in Article 58 of Law No. 36 of 2009 on Health and Article 32 of Law No. 44 of 2009 concerning Hospitals. Keywords: Liability, Civil, Medical Malpractice